2011
DOI: 10.1016/j.jmr.2011.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Spin relaxation and linear-in-electric-field frequency shift in an arbitrary, time-independent magnetic field

Abstract: A method is presented to calculate the spin relaxation times T(1), T(2) due to a non-uniform magnetic field, and the linear-in-electric-field precession frequency shift δω(E) when an electric field is present, in the diffusion approximation for spins confined to a rectangular cell. It is found that the rectangular cell geometry admits of a general result for T(1), T(2), and δω(E) in terms of the spatial cosine-transform components of the magnetic field. The result is applied to the case of a permanently-magnet… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 18 publications
2
15
0
Order By: Relevance
“…The solution of the problem for k = 1 is well known and will be given here for completeness. A general expression for longitudinal relaxation Γ 1 due to 1D diffusive motion reads [3,25,26]:…”
Section: Discussionmentioning
confidence: 99%
“…The solution of the problem for k = 1 is well known and will be given here for completeness. A general expression for longitudinal relaxation Γ 1 due to 1D diffusive motion reads [3,25,26]:…”
Section: Discussionmentioning
confidence: 99%
“…[16] gave analytic expressions for the relevant correlation functions for a gas of particles moving in a cylindrical vessel exposed to a magnetic field with a linear gradient along with an electric field. Petukhov et al [17] and Clayton [18] showed how to determine the correlation functions for arbitrary geometries and spatial field dependence for cases where the diffusion theory applies, while Swank et. al.…”
Section: Introductionmentioning
confidence: 99%
“…Extremely uniform magnetic fields with a high temporal stability are essential to various precision measurements, such as electric dipole moment (EDM) measurements [1][2][3][4] or magnetic field detector calibration [5][6][7] . For the challenging EDM measurements a nonzero magnetic field gradient enhances vibration noise seen by magnetometers 8,9 and shortens the possible measurement time for a single experiment, thus deteriorating its statistical sensitivity [10][11][12] . The final unavoidable field gradient also causes systematic uncertainties like geometric phase shift 13,14 , which is the dominant error contribution to the present neutron EDM upper limit 15 .…”
Section: Introductionmentioning
confidence: 99%